Pengaruh Aspek Fundamental Dan Teknikal Terhadap Harga Saham Perusahaan Perbankan 2019-2021 - Fadillah, Alia Nur (CV. ITTC INDONESIA, 2023)
In investing in shares is not just about including capital into a company, but it is necessary to conduct an analysis to find out the performance of the company, especially in fundamental and technical analysis. The fundamental factors used are variables Earnings Per Share while the technical factors used vary Trading volume, market capitalization, and book value to the market.This study was conducted with the aim of determining the influence of variables Earning Per Share, Trading Volume, Market Capitalization and Book to Market Value on the Stock Price of the Banking Sector listed on the Indonesia Stock Exchange in 2019-2021. This study used a quantitative approach with purposive sampling method. The data used are secondary data and the analysis methods used are panel data regression and multiple linear regression. The results of this study show that partially the variables Earning Per Share, and Market Capitalization have a significant positive effect on stock prices while the variables Trading Volume and Book to Market Value do not have a significant effect on stock prices. And simultaneously the variables Earnings Per Share, Trading Volume, Market Capitalization and Book to Market Value have a significant effect on stock prices.